Single Cell Protein Production Using Different Fruit Waste: A Review - Thiviya, P.; Gamage, A.; Kapilan, R.; Merah, O.; Madhujith, T. (MDPI, 2022)
The single cell protein (SCP) technique has become a popular technology in recent days, which addresses two major issues: increasing world protein deficiency with increasing world popula tion and the generation of substantial industrial wastes with an increased production rate. Global fruit production has increased over the decades. The non-edible parts of fruits are discarded as wastes into the environment, which may result in severe environmental issues. These fruit wastes are rich in fermentable sugars and other essential nutrients, which can be effectively utilized by microorganisms as an energy source to produce microbial protein. Taking this into consideration, this review explores the use of fruit wastes as a substrate for SCP production. Many studies reported that the wastes from various fruits such as orange, sweet orange, mango, banana, pomegranate, pineapple, grapes, watermelon, papaya, and many others are potential substrates for SCP production. These SCPs can be used as a protein supplement in human foods or animal feeds. This paper discusses various aspects in regard to the potential of fruit wastes as a substrate for SCP production
Keywords: Bioconversion;; Fermentation; Fruit wastes; Microbial protein; Single cell protein